Single Nucleotide Polymorphisms of BMP2 Gene Association with Skeletal Class I Crowding: A PCR Study - Madanshetty, Pallavi; Grover, Ishita; Sharma, Kalpesh; Yannawar, Vijay N; Kotalwar, Ganesh R; Lagali, Prashant S (The journal of contemporary dental practice, 2021)
This study is conducted to find the association of BMP2 (bone morphogenic protein 2) gene variant rs1005464 and rs15705 with skeletal class I crowding cases. Blood samples from 60 subjects who visited the Department of Orthodontics and Dentofacial Orthopaedics, D.A.P.M.R.V. Dental College, Bengaluru, were taken after written informed consent. These were divided into two groups: group A with 30 subjects having skeletal class I bases with crowding and group B with 30 subjects having skeletal class I bases without visible crowding or spacing (±2 mm). Around 2 mL of venous blood sample was procured from cases and controls after careful examination. All the samples were then subjected to polymerase chain reaction followed by DNA sequencing and capillary electrophoresis. BMP2 rs1005464 and rs15705 gene variants were assessed and Z-Test was used for statistical analysis. GG ( = 0.001) and CC ( = 0.0024) genotype of BMP2 gene variant rs1005464 and rs15705, respectively, are significantly associated with skeletal class I crowding cases. This study concludes that BMP2 variants rs1005464 and rs15705 can be used as genetic markers for skeletal class I bases having crowding. Predisposing genetic markers BMP2 can be identified prior and this would help in predicting the probability of potential crowding in the future and this would help in early prevention and intervention of crowding.